Management of Student Life Skills and Their Impact on Learning Outcomes of Madrasah Students During The Covid-19 Pandemic Period - Bahiroh, Siti; Madjid, Abd (JURNAL AL-TANZIM, 2022)
This study aims to analyze the mastery of student life skills (personal skills, social skills, academic skills, and vocational skills) and their impact on the learning outcomes of madrasah students during the covid-19 pandemic period. This research is quantitative research that uses the correlational descriptive method. The sample of this study is 64 students of Grade Sixth of Madrasah Ibtidaiyah Muhammadiyah Jragan. The results show that personal skills and social skills significantly affect the learning outcomes of madrasah students. Meanwhile, simultaneously, all life skills variables in this study substantially influence the learning outcomes of Madrasah students. These results indicate that life skills education mastered by madrasah students when studying online at home during the covid-19 pandemic encourages the achievement of good madrasa student learning outcomes. Hence, it can be concluded that online learning at home can work well if it is supported by better mastery of student life skills.